Modeling and analysis of the electrical braking energy of urban railway vehicles. (November 2015) - Yang, Jian; Hou, Yue; Song, Ruigang; Yuan, Tianchen
In this paper, the energy distribution of electrical braking for an urban railway transportation system is studied. In order to calculate the percentage of regenerative and resistance braking energy, line 2 of the Shanghai Metro traction power network is modeled through an analysis approach. An effective method is proposed to establish the equivalent models for each part of the traction power network. The parameters and conditions are based on real parameters from the Shanghai Metro line 2. When the departure interval is 200 seconds, the regenerative braking energy accounts for 71.8% of the total electrical braking energy based on the simulation data and 69.3% of the total electrical braking energy based on the measured data. This paper can provide a theoretical basis for energy-saving evaluation of urban railway transportation systems.